Osteopontin drives KRAS-mutant lung adenocarcinoma. (19th November 2019) - Giopanou, Ioanna; Kanellakis, Nikolaos I; Giannou, Anastasios D; Lilis, Ioannis; Marazioti, Antonia; Spella, Magda; Papaleonidopoulos, Vassilios; Simoes, Davina C M; Zazara, Dimitra E; Agalioti, Theodora; Moschos, Charalampos; Magkouta, Sophia; et al.
Abstract: Increased expression of osteopontin (secreted phosphoprotein 1, SPP1) is associated with aggressive human lung adenocarcinoma (LADC), but its function remains unknown. Our aim was to determine the role of SPP1 in smoking-induced LADC. We combined mouse models of tobacco carcinogen-induced LADC, of deficiency of endogenous Spp1 alleles, and of adoptive pulmonary macrophage reconstitution to map the expression of SPP1 and its receptors and determine its impact during carcinogenesis. Co-expression of Spp1 and mutant Kras G12C in benign cells was employed to investigate SPP1/KRAS interactions in oncogenesis. Finally, intratracheal adenovirus encoding Cre recombinase was delivered to LSL.KRAS G12D mice lacking endogenous or overexpressing transgenic Spp1 alleles. SPP1 was overexpressed in experimental and human LADC and portended poor survival. In response to two different smoke carcinogens, Spp1 -deficient mice developed fewer and smaller LADC with decreased cellular survival and angiogenesis. Both lung epithelial- and macrophage-secreted SPP1 drove tumor-associated inflammation, while epithelial SPP1 promoted early tumorigenesis by fostering the survival of KRAS -mutated cells. Finally, loss and overexpression of Spp1 was, respectively, protective and deleterious for mice harboring KRAS G12D -driven LADC. Our data support that SPP1 is functionally involved in early stages of airway epithelial carcinogenesis driven by smoking and mutant KRAS and may present an important therapeutic target. Abstract : Here, we used mouse models of chemically and genetically induced LADC combined with mice engineered to lack or overexpress osteopontin genes and with human observations to identify osteopontin's exact role during lung tumor development.